Síntese, caracterização e cristaloquímica de complexos da cobre(I) e mercúrio(II) com ligantes triazenidos - Bonini, Janaína Sartori (2005)
The reaction between mercury(II) acetate and 1-(3-nitrophenyl)-3-(2-fluorophenyl)triazene in a tetrahydrofuran/methanol mixture in the presence of 2,2′-bipiridylamine yields the complex [Hg(FC6H4NNNC6H4NO2)2] (1). (1) crystallizes in the triclinic crystal system, space group P(-1), with the crystal data a = 6,8318(10) Å, b = 8,271(3) Å, c = 11,3111(7) Å, α = 72,249(16)°, β = 87,133(9)° e γ = 79,979(17)°, V = 599,4(2) Å³, Z = 2, R1 = 0,0258 and wR2 = 0,0637. The mononuclear complex presents two deprotonated 1-(3-nitrophenyl)-3- (2-fluorophenyl)triazenido monodentate ligands linear coordinated to Hg(II). The crystal structure is characterized by chains of molecules of (1) along the crystallographic direction [100] as result from intermolecular metal-arene π interactions. The reaction between tetrakis(triphenylphosphine)copper(I) chloride and 1,3- bis(4-nitrophenyl)triazene previously deprotonated with metallic sodium in methanol yields the complex [Cu(NO2C6H4N-NNC6H4NO2)(PPh3)2] (2). (2) crystallizes in the monoclinic crystal system, space group P21/c, with the crystal data a = 15,8852(3) Å, b = 11,9539(3) Å, c = 23,2094 Å, β = 94,6460(10)°, V = 4392,75(18) Å³, Z = 4, R1 = 0,0446 and wR2 = 0,1089. The crystal structure of (2) is built by discrete mononuclear complexes in which the Cu(I) ion presents a distorted tetrahedral coordination geometry. One deprotonated 1,3-bis(4-nitrophenyl)triazenide ion act as a bidentate ligand, while two neutral triphenilphosphine molecules completes the coordination sphere of the metal ion. The crystal structure reveals molecules of (2) related by an axial c-glide plane and by an axial 21-two-fold screw axis resulting chains along the [001] and [010] directions via intermolecular C−H...O no classic hydrogen bonds. Beside the single crystal structure analysis, both the complexes (1) and (2) were also characterized by melting point determination and infrared spectroscopy.